Astigmatism and its components in 12-year-old Chinese children: the Anyang Childhood Eye Study. Issue 6 (2nd August 2018) - Li, He; Li, Shi-Ming; Liu, Luo-Ru; Ji, Ya-Zhou; Kang, Meng-Tian; Gan, Jia-He; Bai, Ya-Wen; Yan, Ran; Zhan, Si-Yan; Mitchell, Paul; Wang, Ningli; Atchison, David A
Abstract : Purpose: To determine prevalence of refractive (RA), corneal (CA) and internal astigmatism (IA), including variation with gender and spherical equivalent refraction (SE), in a population of 12-year-old Chinese children. Methods: A total of 1783 students with a mean age of 12.7 years (range 10.0–15.6 years) completed comprehensive eye examinations in the Anyang Childhood Eye Study. Data of cycloplegic refraction and corneal curvature were analysed. Results: Prevalences of RA, CA and IA ≥1.0 D were 17.4% (95%CI 15.6% to 19.2%), 52.8% (50.5% to 55.1%)%) and 20.9% (19.0% to 22.8%), respectively. With different limits of astigmatism axes classification, including ±15°,  ±20° and ±30°, RA and CA axes were mainly 'with-the-rule' (WTR) (ie, correcting axis of negative cylinders at or near 180°), while those for IA axes were mainly 'against-the-rule' (ATR) (ie, correcting axis of negative cylinders at or near 90°). RA was not different between the genders, but girls had higher prevalence and greater means of CA and IA. RA and CA increased in students with higher ametropia (more myopia and more hyperopia) and were the highest in a high myopic group (SE≤−6 D), while IA was stable across refraction groups. Children with RA higher than 0.50 D were more likely to have lens corrections (51%, 57%, 61% and 69% for magnitudes of ≥0.50 D,  ≥0.75 D,  ≥1.0 D and ≥1.5 D, respectively). Conclusions: Prevalence of RA in the Chinese 12-year-old children was relatively high compared with other studies. RA and CA had mainly 'WTR' astigmatism, while IA was mainly ATR and partially compensated for CA. Girls had greater means and prevalences of CA and IA than did boys. Both RA and CA, but not IA, increased with refractive errors away from emmetropia.